Quality of life and metabolic control in type 2 diabetes mellitus diagnosed individuals. Issue 5 (September 2019) - Cepeda Marte, Jenny L.; Ruiz-Matuk, Carlos; Mota, Merary; Pérez, Sabrina; Recio, Natasha; Hernández, Deysi; Fernández, José; Porto, Jackie; Ramos, Angel
Abstract: Aims: Determine the correlation of quality of life (QoL) and the impact on the metabolic control of patients with type 2 diabetes mellitus (T2DM). Methods: An observational study was conducted at the outpatient consulting service in a specialized hospital in Santo Domingo, DR. We used a non-probabilistic, convenience sampling strategy, and the World Health Organization Quality of Life (WHOQOL-BREF) short form questionnaire was applied. Results: The patients presented lower impact in QoL domains was: pain ( x ¯ = 29.07, SD = 3.04) and negative feelings ( x ¯ = 28.70, SD = 3.33). We found there is a negative correlation between the psychological domains and the fasting glycemia ( r ho  = −0.192, p  < 0.05), also between the summary of all domains of QoL and metabolic control, HbA1C ( r ho  = −0.205, p  < 0.05), and fasting glycaemia ( r ho  = −0.214, p  < 0.05). There was a significant difference in the physical domains F (1, 131) = 9.73, p  = 0.002, η 2  = 0.069, indicating that men ( M  = 14.81) have a higher physical QoL than women ( M =  13.72). Conclusion: Given the evidence of the impact of metabolic control and the different domains to QoL, it is necessary to consider these aspects in the treatment plan of patients with diabetes, to ensure adequate management and control of future complications.